2011
DOI: 10.3109/00365548.2011.598872
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features of Turkish children with 2009 pandemic influenza A (H1N1) infection: Experience from multiple tertiary paediatric centres in Turkey

Abstract: In Turkey, 2009 H1N1 infection caused high mortality and PICU admission due to severe respiratory illness and complications, especially in children with an underlying condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
20
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 14 publications
8
20
0
9
Order By: Relevance
“…Our pandemic hospitalization data showed similarities with other countries: the median age (5 years) of children hospitalized was similar to that found in large studies in Canada and Korea, but slightly lower than that found in Japan [18][19][20]. There were more males than females hospitalized in Ireland during the pandemic, as was found in many other studies [19,27,28]. 43% in Germany, and 42% of cases in Australia [5,21], but in line with or higher than other large populationbased studies (32% in the USA, 27·5% in Madrid and 22·4% in Korea) [6,22,23].The proportion of hospitalized children requiring PICU admission was low at 5% when compared with that found in Canada and Argentina at 16·8% and 19% respectively, but similar to Australia at 4·6% [6,21,24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Our pandemic hospitalization data showed similarities with other countries: the median age (5 years) of children hospitalized was similar to that found in large studies in Canada and Korea, but slightly lower than that found in Japan [18][19][20]. There were more males than females hospitalized in Ireland during the pandemic, as was found in many other studies [19,27,28]. 43% in Germany, and 42% of cases in Australia [5,21], but in line with or higher than other large populationbased studies (32% in the USA, 27·5% in Madrid and 22·4% in Korea) [6,22,23].The proportion of hospitalized children requiring PICU admission was low at 5% when compared with that found in Canada and Argentina at 16·8% and 19% respectively, but similar to Australia at 4·6% [6,21,24,25].…”
Section: Discussionsupporting
confidence: 88%
“…The most common symptoms at presentation are reported as fever, cough and respiratory problems in most reports . Similarly, in our study, fever and cough were the most common clinical signs (85.7%), followed by fatigue (57%).…”
Section: Discussionsupporting
confidence: 82%
“…from Canada but more than Çiftçi et al . from Turkey . Digestive symptoms tend to be more common than seasonal influenza infection, which is detected as 23.8% diarrhea and 38% as vomiting in our study .…”
Section: Discussionmentioning
confidence: 43%
“…The majority of admitted children (56.9%) were younger than 5 y of age, and 35 children (4.3%) died. The death rate was significantly higher in patients with malignancy, chronic neurological disease, immunosuppressive therapy, at least 1 pre-existing condition, or respiratory complications [11]. …”
Section: Discussionmentioning
confidence: 99%